1995
DOI: 10.1016/0092-8674(95)90358-5
|View full text |Cite
|
Sign up to set email alerts
|

A molecular basis for cardiac arrhythmia: HERG mutations cause long QT syndrome

Abstract: To identify genes involved in cardiac arrhythmia, we investigated patients with long QT syndrome (LQT), an inherited disorder causing sudden death from a ventricular tachyarrythmia, torsade de pointes. We previously mapped LQT loci on chromosomes 11 (LQT1), 7 (LQT2), and 3 (LQT3). Here, linkage and physical mapping place LQT2 and a putative potassium channel gene, HERG, on chromosome 7q35-36. Single strand conformation polymorphism and DNA sequence analyses reveal HERG mutations in six LQT families, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1,168
2
18

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,110 publications
(1,190 citation statements)
references
References 31 publications
2
1,168
2
18
Order By: Relevance
“…The`Human ether-a-go-go-related Gene' (HERG) is now widely accepted as encoding the a-subunit of channels carrying I Kr ; polymorphisms in HERG can impair channel function and thereby lead to chromosome-7-linked long QT syndrome (LQTS ± LQT2; Curran et al, 1995;Sanguinetti et al, 1996a). Moreover, when HERG was ®rst identi®ed as encoding an I Kr -like channel, it was suggested that it may also mediate the`acquired' (drug-induced) form of the syndrome (Sanguinetti et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The`Human ether-a-go-go-related Gene' (HERG) is now widely accepted as encoding the a-subunit of channels carrying I Kr ; polymorphisms in HERG can impair channel function and thereby lead to chromosome-7-linked long QT syndrome (LQTS ± LQT2; Curran et al, 1995;Sanguinetti et al, 1996a). Moreover, when HERG was ®rst identi®ed as encoding an I Kr -like channel, it was suggested that it may also mediate the`acquired' (drug-induced) form of the syndrome (Sanguinetti et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The long QT syndrome (LQTS) is characterized by prolongation of the QT interval and T wave abnormalities on electrocardiograms (ECG) [1,2]. LQTS is associated with symptoms including syncope, seizures and sudden death caused by a specific ventricular arrhythmia, torsade de pointes [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…LQTS is associated with symptoms including syncope, seizures and sudden death caused by a specific ventricular arrhythmia, torsade de pointes [1,2]. One of the major genes identified for LQTS is the SCN5A gene on chromosome 3p21-23 (LQT3), which accounts for 10-20% LQTS cases [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Concretamente, en los ú ltimos 30 añ os se han producido los siguientes grandes avances, que ciertamente constituyen hitos en la medicina moderna y configuran la arritmología como una parte de la cardiología con personalidad bien definida que debe constituir una unidad propia dentro de los servicios de cardiología. Los cambios má s relevantes son los siguientes: a) la aparició n de las té cnicas de ablació n 1,2 , que han revolucionado el tratamiento de las taquiarritmias supraventriculares y ventriculares y ya han demostrado su eficacia en una arritmia tan prevalente como la fibrilació n auricular; b) la eficacia de los desfibriladores automá ticos implantables para evitar la muerte sú bita 3 ; c) la utilidad de los marcapasos de resincronizació n para tratar a un nú mero importante de pacientes con insuficiencia cardiaca 4 , y d) la identificació n de nuevas entidades arritmogé nicas de origen gené tico, las canalopatías, que explican la muerte sú bita inesperada, sobre todo en jó venes [5][6][7] .Como en ediciones previas de REVISTA ESPAÑ OLA DE CARDIOLOGÍA 8-10 , en esta nueva edició n de «Puesta al día» de 2012, hemos conseguido reunir a «primeras espadas» para cada una de las facetas de las arritmias, con la finalidad de poner a disposició n del cardió logo clínico, el residente de cardiología y el mé dico internista y de familia interesado en el tema las bases anató micas y electrofisioló gicas necesarias para conocer su mecanismo y aprender a diagnosticarlas y tratarlas con precisió n.El primer capítulo de esta serie de «Puesta al día» se centra en un aspecto organizativo y de gestió n: la estructuració n de una unidad de arritmias en el siglo XXI. Las unidades de arritmias son cada vez má s complejas, y sus integrantes deben ocuparse de las consultas específicas (primeras visitas y visitas sucesivas), la implantació n y el seguimiento de dispositivos (tanto in situ como a distancia) y las ablaciones (de cavidades derechas e izquierdas), ademá s de la dedicació n a aspectos docentes y de investigació n. El Dr. Kuck propone un modelo organizativo eficiente y moderno.…”
unclassified
“…Concretamente, en los ú ltimos 30 añ os se han producido los siguientes grandes avances, que ciertamente constituyen hitos en la medicina moderna y configuran la arritmología como una parte de la cardiología con personalidad bien definida que debe constituir una unidad propia dentro de los servicios de cardiología. Los cambios má s relevantes son los siguientes: a) la aparició n de las té cnicas de ablació n 1,2 , que han revolucionado el tratamiento de las taquiarritmias supraventriculares y ventriculares y ya han demostrado su eficacia en una arritmia tan prevalente como la fibrilació n auricular; b) la eficacia de los desfibriladores automá ticos implantables para evitar la muerte sú bita 3 ; c) la utilidad de los marcapasos de resincronizació n para tratar a un nú mero importante de pacientes con insuficiencia cardiaca 4 , y d) la identificació n de nuevas entidades arritmogé nicas de origen gené tico, las canalopatías, que explican la muerte sú bita inesperada, sobre todo en jó venes [5][6][7] .…”
unclassified